The Effect of Financial Literacy, E-Money Use and Self-Control on Consumptive Behavior - Light, November; Poniman, Poniman (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Consumptive behavior is the act of consuming an item or service excessively with high intensity that tends to prioritize wants over needs. The study aims to determine the effect of financial literacy, e-money usage, and self-control on the consumptive behavior of accounting students in Batam city. The total population was 1,354 accounting students with a sample of 93 accounting students. This study uses a quantitative approach with simple random sampling technique using primary data obtained from distributing questionnaires online using google form. The data in this study were processed using SPSS (Statistical Package for Social Science) software version 26. The data analysis technique in this study used validity test, reliability test, classical assumption test and hypothesis testing. The results of the t test research explain that financial literacy and the use of e-money partially have no effect on the consumptive behavior of accounting students. Self-control partially affects the consumptive behavior of accounting students. The results of the F test research explain that financial literacy, e-money usage, self-control simultaneously have a significant effect on the consumptive behavior of accounting students with a percentage of 17.9% and the remaining 82.1% is influenced by other variables.